JALAN ANALISIS PENGARUH BEBAN LALU LINTAS TERHADAP UMUR RENCANA - Siprianus Satriawan; Widarto Sutrisno; Detha Sekar Langit Wahyu Gutama (Department of Civil Engineering, Faculty of Engineer, Universitas Sarjanawiyata Tamansiswa, 2024)
Godean Road is one of the roads whose traffic volume is quite dense, causing a decrease in the planned life of this road. Some of the factors that make this road experience a decrease in the planned life are high traffic volume, vehicle axle loads, and also vehicle loads. Based on this, the author conducted research on the road using the Bina Marga Method and the 1993 ASSHTO Method. The Bina Marga method (Pavement Design Manual 2017) is used to calculate average daily traffic and calculate vehicle equivalent numbers. Based on the results of data analysis using the Bina Marga Method (Pavement Design Manual 2017), it was found that the average daily traffic on the Godean road of Sleman DIY district was 78887 vehicles / day / direction, and the equivalent number of each vehicle was obtained, light vehicles 0.0024, pick ups 0.0206, small buses 0.31545, large buses 0.38424, 2-axis light trucks 3.048, 2-axis medium trucks 6.422, 3-axis trucks 5.2418, trailer trucks 6.708, and semi trailer trucks 5.182. The ASSHTO 1993 method is used to calculate the remaining life of the road plan. Based on the results of data analysis, it is obtained that the percentage of road reduction rates on the Godean road is 40%, a reduction of 60%.